بیست و یکمی صدی ٹی براہوئی زبان نا آخبت، ویل و گڑتیک: The Problems and future of Brahui language in 21th Century - Jalil Ahmed Mengal; Dr.Manzoor Baloch (Al-Burz, 2018)
According to UNESCO 2008 report, 2500 languages are endangered in the world, 27 of them exist in Pakistan. Brahui language is also one of them. In this research paper it would be try to shed some spotlight on the real status of Brahui language, whether the Brahui language is endangered or it is still safe. According to UNESCO report the cause of endangerment of Brahui language is because of the less speakers but at the same time it is interesting to note here that Brahui speakers are present from Balochistan to Afghanistan? Iran and Turkmenistan. The real cause of endangerment of the Brahui language will be tried to evaluate in this article.